Built environment and car driving distance in a small city context - Fitwi Wolday (Journal of Transport and Land Use)
This article focuses on the effect of built-environment factors on travel behavior in the context of small cities. Urban size and spatial context are central to travel behavior analysis because of the spatiotemporal nature of transportation. Different urban structural attributes exert travel behavioral influences at different spatial scales (local vs. regional) and urban sizes. Due to this inherent geographic dimension in travel studies, findings from larger urban areas may not be transferable to small cities. Despite this, however, small cities remain scantily represented in the literature. Using multivariate analysis on survey data from three small cities in Norway, this paper finds that the built-environment effects on travel behavior are highly influenced by regional characteristics and the city’s center structure (poly-centered vs. single centered). Residential proximity to the city center leads to reduced car driving distance through its distance-minimizing effect to concentrations of facilities for local travel. At the regional scale, proximity to the city center influences car driving distance via the higher likelihood among centrally located commuters of choosing transit as their commute mode.